ON MINIMAL COSET COVERING OF SOLUTIONS OF A BOOLEAN EQUATION - Minasyan, A.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
For the equation x_1x_2… x_n+x_n+1x_n+2… x_2n+x_2n+1x_2n+2… x_3n=1 over the finite field F_2 we estimate the minimal number of systems of linear equations over the same field such that the union of their solutions exactly coincides with the set of solutions of the equation. We prove in this article that the number in the question is not greater than 9n^_2 3+4.